Residual Stress in Engineering Materials: A Review - Tabatabaeian, Ali; Ghasemi, Ahmad Reza; Shokrieh, Mahmood M.; Marzbanrad, Bahareh; Baraheni, Mohammad; Fotouhi, Mohammad (Advanced engineering materials, 2022)
The accurate determination of residual stresses has a crucial role in understanding the complex interactions between microstructure, mechanical state, mode(s) of failure, and structural integrity. Moreover, the residual stress management concept contributes to industrial applications, aiming to improve the product's service performance and life cycle. In this regard, the industry requests rapid, efficient, and modern methods to identify and control the residual stress state. This review article contains three main sections. The first section covers different residual stress determination methods and reports the advancements over the recent decade. The second section includes the role of residual stresses in the performance of a broad range of materials including metallic alloys, polymers, ceramics, composites, and biomaterials. This is presented by classifying different science areas dealing with residual stresses into two main groups, including “origins” and “effects” of residual stresses. The range of topics covered are “welding, machining, curing/cooling, and spray coating processes,” “medical and dental sciences,” and “fatigue and fracture mechanisms.” The third section summarizes various strategies to effectively control residual stresses through different manufacturing procedures. It is hoped that the data provided herein serves as a valuable up‐to‐date reference for engineers and scientists in the field of residual stress. The accurate determination of residual stresses has a crucial role in understanding the complex interactions between microstructure, mechanical state, mode(s) of failure, and structural integrity. Herein, different residual stress determination methods and reports the advancements over the recent decade. Also, the role of residual stresses in the performance of a broad range of materials is discussed, and, finally, various strategies to effectively control residual stresses through different manufacturing procedures are summarized.